Multifaceted properties of Ni and Zn codoped MgO nanoparticles - A. Chithra Mohan; A. Athira; Bindu P. Nair; G. Sivasubramanian; K. M. Sreekanth; Gopinathan Anoop; Sreeprasanth Pulinthanathu Sree; K. M. Sreedhar (Scientific Reports)
Abstract Recent advancements in material science have aimed to create novel nanomaterials with unique properties and potential applications across diverse domains. By deciphering the complexities of the versatile nanomaterial, MgO, the study aims to deepen our comprehension of the synergistic effects induced by dual doping in MgO, thus propelling the advancement of innovative technologies and materials with broad applications. The present investigation employed a facile chemical precipitation and coprecipitation approach to synthesize pure MgO and Ni, Zn dual doped MgO, varying Ni concentration ranging between 2% and 10% and maintaining a constant Zn concentration at 20%. Structural and optical properties were investigated using field emission scanning electron microscope, energy dispersed X-ray analysis, powder X-ray diffraction, absorption spectra, besides photoluminescent analysis. Crystallite size, strain value then dislocation density of the samples were estimated by Scherrer equation and Williamson–Hall method. Tauc plot analysis revealed that codoped samples reduces the bandgap of MgO. The PL emission spectra exhibited a broad emission originating from various defect levels induced by Ni and Zn codoping in MgO. Ferromagnetism was also induced in Ni and Zn codoped samples with a saturation magnetization up to 5.4668 × 10−3 emu for 10%Ni–20%Zn doped MgO. The antibacterial studies were carried out and all samples were effective against the Staphylococcus aureus strain (ATCC 25923). This thorough investigation highlights the multidimensional impact of Ni, Zn dual doping on the characteristics of MgO nanoparticles, offering valuable insights for diverse applications in materials research.